2015
DOI: 10.1109/tits.2014.2372000
|View full text |Cite
|
Sign up to set email alerts
|

GPS Signal Authentication From Cooperative Peers

Abstract: Grace Xingxin Gao (M'12) received the B.S. degree in mechanical engineering and the M.S. degree in electrical engineering

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 20 publications
1
45
0
1
Order By: Relevance
“…Other works in literature have studied the use of multiple receivers to detect GPS spoofing attacks such as in [22]- [24]. In [22], the authors demonstrated the ability of using a dual antenna receiver in detecting GPS spoofing attacks.…”
Section: Arxiv:190411568v3 [Cssy] 29 Dec 2019mentioning
confidence: 99%
See 1 more Smart Citation
“…Other works in literature have studied the use of multiple receivers to detect GPS spoofing attacks such as in [22]- [24]. In [22], the authors demonstrated the ability of using a dual antenna receiver in detecting GPS spoofing attacks.…”
Section: Arxiv:190411568v3 [Cssy] 29 Dec 2019mentioning
confidence: 99%
“…However, under a GPS spoofing attack, the measured distances will be very close to zero, as all the receivers are spoofed with the same fake location. Finally, in [24], multiple receivers were used to authenticate the GPS signals based on the correlation with the military GPS signal, without the need to decrypt it. Among these receivers, one GPS receiver uses the other receivers, referred to as cross-check receivers, to determine whether its GPS signals are authentic.…”
Section: Arxiv:190411568v3 [Cssy] 29 Dec 2019mentioning
confidence: 99%
“…Subsequent risk is related to location-related attacks. The GPS signal could be vulnerable to position lock (jamming) or to feeding the receiver with false information, so that it computes an erroneous time or location (spoofing) [190,191]. Similar techniques may be applied to cellular-and WLAN-based location services [192,193].…”
Section: Security and Privacymentioning
confidence: 99%
“…The open GNSS signal does not inherently carry any ''built-in'' anti-interference method; therefore, it is vulnerable to radio-frequency attacks that aim either at blinding the receiver or fooling it. The first condition is typically indicated as jamming, as in the case of Grant et al (2009), while the second is known as spoofing (Heng et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The major hazard in this situation is that the receiver is typically not aware of being fooled; therefore, it does not raise any alarm to the hosting system, which is induced to make wrong and possibly hazardous decisions based on spoofed PNT information. The recent literature has highlighted the risk of intentional attackers willing to interfere with the correct GNSS receiver functions (Heng et al 2015;Akos 2012).…”
Section: Introductionmentioning
confidence: 99%